The demographic consequences of sex-selection technology - Qi Li; Juan Pantano (Quantitative Economics, 2023)
Over the last several years, highly accurate methods of sex selection before conception have been developed. Given that strong preferences for sex variety in off- spring have been documented for the U.S., we ask what the demographic conse- quences of sex-selection technology could be. Lacking variation across space and time in access to this technology, we estimate a dynamic programming model of fertility decisions with microdata on fertility histories. We leverage the quasi- experimental variation inherent in the random determination of sex to identify the key structural parameter characterizing preferences for sex variety in off- spring. We then simulate the introduction of this technology. While this technol- ogy can reduce fertility by allowing parents to efficiently reach their preferred sex mix, it could also increase it. This is because without this technology, many par- ents may opt not to have another baby given the uncertainty about its sex. Results suggest that these two effects operate simultaneously, but on net, sex-selection technology ends up reducing the average family size among married women by less than 2% in the steady state, a much smaller decline than the one that would be predicted by alternative methods.
Keywords: J11; J13; 330; Sex-selection; fertility